(untitled) (Proceedings of International Educators Conference, 2024)
Diabetic nephropathy (DN) is a serious complication of diabetes mellitus, characterized by progressive kidney dysfunction. Studying renal biomarkers is crucial for understanding the pathophysiology of DN and developing effective management strategies. In this study, we compared glomerular filtration rate (GFR) calculated using the creatinine-cystatin C formula, levels of albuminuria, and concentrations of klotho protein in the blood between control group patients and those with diabetic nephropathy.